Gamma-cyclodextrin crystal form and preparation method thereof
By adding hydroxypropyl methylcellulose in the preparation process of γ-cyclodextrin and performing program-raising and cooling and crystallization, γ-cyclodextrin with crystal form A was successfully prepared, which solved the problems of unstable and low bulk density of γ-cyclodextrin in the prior art, achieving higher stability and bulk density, and is suitable for applications in the pharmaceutical and food industries.
Patent Information
- Application Number
- CN202311209799.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to prepare stable and high bulk density γ-cyclodextrin crystal forms, resulting in bioavailability and stability problems in applications in the pharmaceutical and food industries.
By sealing the γ-cyclodextrin with water and heating until dissolved, filtration was added, hydroxypropyl methylcellulose was added, and treatment was carried out under the condition of rising and lowering of the process, γ-cyclodextrin with crystal form A was successfully prepared.
The prepared γ-cyclodextrin crystal form A is more stable than amorphous solids and has a higher bulk density, which improves the packaging stability and transportation efficiency of the product, while reducing transportation costs and storage space.
Smart Images

Figure CN119661746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical raw materials for food, cosmetics and medicine, and in particular to a crystal form of gamma-cyclodextrin and a preparation method thereof. Background Art
[0002] Cyclodextrin (CD) is a general term for a series of cyclic oligosaccharides produced by amylose under the action of cyclodextrin glucosyltransferase produced by Bacillus, usually containing 6 to 12 D-pyranose units. Among them, the molecules containing 6, 7, and 8 glucose units are studied more and are of great significance, which are called α-, β-, and γ-cyclodextrin respectively.
[0003] Since cyclodextrin is hydrophilic on the outside and hydrophobic in the inside, it can provide a hydrophobic binding site like an enzyme, and act as a host to encapsulate various appropriate guests. This property enables it to form inclusion complexes and molecular assembly systems with many organic and inorganic molecules based on van der Waals forces, hydrophobic interactions, and matching effects between host and guest molecules. Therefore, cyclodextrin is widely used in the food and pharmaceutical industries and has become a research object of interest to chemical and chemical researchers. In addition, the high electron density in the cyclodextrin cavity can mobilize the electrons of the contained guest molecules, resulting in changes in various spectral properties of the guest and cyclodextrin itself. The effect of cyclodextrin on the spectral properties of guest molecules makes it used as a reagent for various spectral analyses, including UV-visible spectrophotometry, fluorescence and phosphorescence methods, and nuclear magnetic resonance spectroscopy. For example, Szejtli specifically reviewed the application of cyclodextrin in chromatographic separation and fluorescence spectroscopy.
[0004] γ-cyclodextrin has a larger cavity than α- and β-cyclodextrin, so the cavity can contain a wider range of guest molecules; it has better water solubility. At room temperature of 25°C, the solubility of γ-cyclodextrin is 25.6g / 100ml, while the solubility of α-cyclodextrin is 12.7g / 100ml water and the solubility of β-cyclodextrin is only 1.88g / 100ml water; in addition, the toxicity and irritation of γ-cyclodextrin are very small, and it is highly safe, and its application prospects are broader than those of α- and β-cyclodextrin. Its structural formula is shown in Formula I:
[0005]
[0006] As we all know, compounds usually exist in different solid forms, including polymorphs, hydrates, solvates, salt forms, cocrystals and amorphous forms. Due to different crystal structures, different crystal forms will show significantly different physical and chemical properties, such as solubility, stability, hygroscopicity, etc. γ-cyclodextrin is widely used in the pharmaceutical and food industries, and crystal form research should also be paid attention to, especially in the drug development stage. Insufficient crystal form research will cause various problems in the API molecules due to polymorphism, such as bioavailability, stability, etc. These problems will affect the entire process of drug development and affect the quality and safety of drugs after they are put on the market.
[0007] A Chinese invention patent entitled "A method for producing γ-cyclodextrin" (publication number: CN105039462A, publication date: 20151111) discloses a method for producing γ-cyclodextrin, in which γ-cyclodextrin is prepared by slurry freeze-drying. At present, the crystallization process of γ-cyclodextrin commonly uses spray drying, freeze drying or anti-solvent addition methods, but experiments have shown that the solids obtained by these methods are amorphous. Amorphous γ-cyclodextrin has low bulk density, high energy, and is unstable, making it inconvenient to package, transport and store. According to research, no crystal form of γ-cyclodextrin has been reported. Summary of the invention
[0008] In view of the above-mentioned shortcomings of the prior art, the inventors of the present application discovered the crystal form A of γ-cyclodextrin during the experiment. In a first aspect, the present invention provides a γ-cyclodextrin shown in Formula I, wherein the γ-cyclodextrin has a crystal form A, and the crystal form A has a characteristic peak at at least one of the 2θ values selected from 9.15°±0.2°, 12.04°±0.2° or 16.35°±0.2° as determined by X-ray powder diffraction using Cu-Kα radiation. .
[0009]
[0010] In some embodiments of the present invention, the crystalline form A has a characteristic peak at at least one of the 2θ values selected from 8.98°±0.2°, 9.15°±0.2°, 10.79°±0.2°, 11.16°±0.2°, 12.04°±0.2°, 15.73°±0.2°, 16.35°±0.2°, 18.27°±0.2° or 27.30°±0.2° as determined by X-ray powder diffraction.
[0011] In some embodiments of the present invention, the crystalline form A is determined by X-ray powder diffraction at a 2θ value selected from 4.46°±0.2°, 8.98°±0.2°, 9.15°±0.2°, 9.94°±0.2°, 10.79°±0.2°, 11.16°±0.2°, 11.90°±0.2°, 12.04°±0.2°, 14.10°±0.2°, 15.55°±0.2°, 15.73°±0.2°, At least one of the following has a characteristic peak: 0.2°, 16.35°±0.2°, 16.88°±0.2°, 17.68°±0.2°, 18.27°±0.2°, 19.33°±0.2°, 20.89°±0.2°, 22.05°±0.2°, 22.41°±0.2°, 22.76°±0.2°, 23.86°±0.2°, 24.73°±0.2° or 27.30°±0.2°.
[0012] In some embodiments of the present invention, the crystalline form A is determined by X-ray powder diffraction at a 2θ value selected from 4.46°±0.2°, 5.33°±0.2°, 7.78°±0.2°, 8.98°±0.2°, 9.15°±0.2°, 9.61°±0.2°, 9.94°±0.2°, 10.63°±0.2°, 10.79°±0.2°, 11.16°±0.2°, 11.42°±0.2°, 11.55°±0.2°, 11.90°±0.2°, 12.04°±0.2°, 12.89°±0.2°. °, 13.12°±0.2°, 14.10°±0.2°, 14.42°±0.2°, 15.25°±0.2°, 15.55°±0.2°, 15.73°±0.2°, 16.35°±0.2°, 16.88°±0.2°, 17.68°±0.2°, 18.27°±0.2°, 19.16°±0.2°, 19.33°±0.2°, 19.64°±0.2°, 20.00°±0.2°, 20.89°±0.2°, 21.03°±0.2°, 21.75°±0.2°, 22 .05°±0.2°, 22.41°±0.2°, 22.76°±0.2°, 23.61°±0.2°, 23.86°±0.2°, 24.26°±0.2°, 24.73°±0.2°, 25.57°±0.2°, 25.75°±0.2°, 26.29°±0.2°, 26.61°±0.2°, 26.97°±0.2°, 27.30°±0.2°, 27.44°±0.2°, 28.24°±0.2°, 28.49°±0.2°, 28.66°±0.2°, 29.66° ±0.2°, 30.08°±0.2°, 30.75°±0.2°, 31.71°±0.2°, 32.00°±0.2°, 32.00°±0.2°, 32.88°±0.2°, 33.21°±0.2°, 34.54°±0.2°, 34.69°±0.2°, 35.60°±0.2°, 35.86°±0.2°, 36.14°±0.2°, 38.23°±0.2°, 40.40°±0.2°, 45.94°±0.2° or 48.56°±0.2° has a characteristic peak.
[0013] Furthermore, the X-ray powder diffraction spectrum of the crystal form A of the present invention has the 2θ data shown in Table 1 below:
[0014] Table 1
[0015]
[0016]
[0017]
[0018] In some embodiments of the present invention, the conditions for the X-ray powder diffraction measurement are: X-ray: Cu-Kα radiation; other conditions are that the X-ray light source is Cu The voltage was 40 kV; the current was 40 mA; the scanning range was 3.0° to 50°; the scanning step was 0.02°; and the scanning speed was 6° / min.
[0019] In some embodiments of the present invention, the crystal form A is also measured by differential scanning calorimetry, and the crystal form A exhibits an endothermic peak at least at 70-120° C. when measured by DSC.
[0020] In some embodiments of the present invention, the crystal form A is also measured by differential scanning calorimetry, and the crystal form A decomposes at 285-295° C. as measured by DSC.
[0021] Preferably, the crystalline form A decomposes at 290° C. as measured by DSC.
[0022] In some embodiments of the present invention, the DSC method is carried out under the following conditions: a scanning rate of 10°C / min; the protective gas is nitrogen with a nitrogen flow rate of 50 ml / min; and the temperature range is from room temperature to 330°C.
[0023] In some embodiments of the present invention, the crystal form A is also measured by thermogravimetric analysis, and the weight loss of the crystal form A when heated from room temperature to 300° C. as measured by TGA is 10-15%.
[0024] Preferably, the weight loss of the crystalline form A when heated from room temperature to 200° C. as measured by TGA method is no more than 10.5%.
[0025] More preferably, the weight loss of the crystalline form A when heated from room temperature to 200° C. is 10% as measured by TGA method.
[0026] Furthermore, the γ-cyclodextrin crystal form A has a maximum weight loss rate within the range of 90 to 100°C.
[0027] In some embodiments of the present invention, the TGA method is performed under the following conditions: a scanning speed of 10°C / min; the protective gas is nitrogen with a nitrogen flow rate of 50 ml / min; and the temperature range is from room temperature to 330°C.
[0028] The room temperature is 20-30°C.
[0029] The second aspect of the present invention provides a method for preparing the above-mentioned γ-cyclodextrin crystal form A, wherein the preparation method (1) comprises the following steps:
[0030] (11) adding water to γ-cyclodextrin, sealing the mixture, and placing the mixture in a biochemical incubator to heat the mixture until it becomes clear, thereby obtaining a clear solution;
[0031] (12) The clear solution is filtered and placed in a container, hydroxypropyl methylcellulose is added, and nitrogen is introduced after vacuuming. The container is sealed and placed in a biochemical incubator for programmed temperature rise and fall crystallization, and the precipitated white clustered solid is separated to provide γ-cyclodextrin having a crystalline form A.
[0032] The container is a nuclear magnetic tube.
[0033] The method (1) includes any one or more of the following conditions:
[0034] (111) In step (11), the ratio of the added mass of γ-cyclodextrin to the added volume of water is 1:1-3 g / mL; preferably, the ratio of the added mass of γ-cyclodextrin to the added volume of water is 1:2 g / mL;
[0035] (112) In step (11), the heating temperature is 55-65° C., preferably, the heating temperature is 60° C.;
[0036] (113) In step (11), the heating time is 15-20 min, preferably, the heating time is 15 min;
[0037] (121) In step (12), the filtration is performed by centrifuging to separate the solid and liquid phases;
[0038] (122) In step (12), the amount of hydroxypropyl methylcellulose added is 4-6% by weight of the amount of γ-cyclodextrin fed. Preferably, the amount of hydroxypropyl methylcellulose added is 5% by weight of the amount of γ-cyclodextrin fed.
[0039] (123) In step (12), the programmed temperature rise and fall is first maintained at 55-65°C for 1-3 hours, then cooled to 5-10°C at a rate of 0.1-0.5°C / min, and after the program is repeated 2-5 times, the temperature is maintained at 5-10°C for 70-75 hours. Preferably, the programmed temperature rise and fall is first maintained at 60°C for 2 hours, then cooled to 5°C at a rate of 0.1°C / min, and after the program is repeated 2 times, the temperature is maintained at 5°C for 72 hours.
[0040] The third aspect of the present invention provides a gram-scale preparation method of the above-mentioned γ-cyclodextrin crystal form A, wherein the preparation method (2) comprises the following steps:
[0041] (21) Stirring γ-cyclodextrin and water under nitrogen protection until dissolved, and subjecting the obtained reaction solution to a cooling and stirring procedure;
[0042] (22) The reaction solution after the cooling and stirring process is filtered until dry, and the filter cake is collected to provide γ-cyclodextrin having a crystalline form A.
[0043] The method (2) includes any one or more of the following conditions:
[0044] (211) In step (21), the ratio of the added mass of γ-cyclodextrin to the added volume of water is 1:1-3 g / mL; preferably, the ratio of the added mass of γ-cyclodextrin to the added volume of water is 1:2 g / mL;
[0045] (212) In step (21), the nitrogen protection is to connect a nitrogen balloon protection device to the opening of the container;
[0046] (213) In step (21), the stirring temperature is 55-65°C, preferably, the stirring temperature is 60°C;
[0047] (214) In step (21), the stirring time until the solution is clear is 15-20 minutes, preferably, the stirring time until the solution is clear is 15 minutes;
[0048] (215) In step (21), the cooling and stirring procedure is to first cool the reaction solution to 15-20°C and stir for 1-2 hours, then cool it to 8-12°C and stir for 2-3 hours, and finally cool it to 0-4°C and stir for 4-5 hours; preferably, the cooling and stirring procedure is to first cool the reaction solution to 15°C and stir for 1 hour, then cool it to 8°C and stir for 2 hours, and finally cool it to 0°C and stir for 4 hours;
[0049] (216) In step (21), the stirring rate of the cooling stirring process is 220-225 rpm, preferably, the stirring rate is 220 rpm;
[0050] (217) In step (21), seed crystals need to be added during the cooling and stirring procedure, and the amount of seed crystals added is 0.1-0.5% by mass of the γ-cyclodextrin feed amount; preferably, the seed crystals are γ-cyclodextrin having crystal form A, and the amount of seed crystals added is 0.5% by mass of the γ-cyclodextrin feed amount.
[0051] The clear solution is a clear solution in which the γ-cyclodextrin is dissolved in water after heating.
[0052] The beneficial effects of the present invention are as follows: the crystal form A of γ-cyclodextrin has lower energy than the amorphous solid, is more stable, and has a purification effect, and has advantages in physical and chemical properties, preparation processing performance, etc., especially in bulk density. The crystal form A of γ-cyclodextrin has a higher bulk density than the amorphous form, which makes the packaging of γ-cyclodextrin more stable and can better protect the product from damage or deformation; the high-density packaging of γ-cyclodextrin can also save transportation costs, because the same amount of goods occupies a smaller volume, which can reduce the number of transportations and transportation costs; in the warehousing link, high-density packaging can also reduce the storage space occupied and improve the utilization rate of the warehouse. These advantages provide a better choice for the development of drugs containing γ-cyclodextrin, and have very important practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Shown is the X-ray powder diffraction (XPRD) spectrum of the γ-cyclodextrin crystal form A of the present invention.
[0054] Figure 2 The differential scanning calorimetry (DSC) spectrum of the γ-cyclodextrin crystal form A of the present invention is shown.
[0055] Figure 3 Shown is the thermogravimetric analysis (TGA) spectrum of the γ-cyclodextrin crystal form A of the present invention.
[0056] Figure 4 The XRPD pattern of amorphous γ-cyclodextrin is shown. DETAILED DESCRIPTION
[0057] Specific embodiments of the present invention are described with reference to the following examples, which are intended to illustrate the present invention but are not intended to limit the present invention in any way. The raw materials described can be obtained from public commercial sources unless otherwise specified. The instruments involved in the implementation of this application are all common instruments commonly used in the art unless otherwise specified.
[0058] The X-ray powder diffraction (XPRD) pattern of the present invention is measured by: the sample is collected on a Bruker D2PHASER X-ray powder diffractometer; the X-ray light source is Cu The voltage was 40 kV; the current was 40 mA; the scanning range was 3.0° to 50°; the scanning step was 0.02°; and the scanning speed was 6° / min.
[0059] The differential scanning calorimetry (DSC) spectrum determination method involved in the present invention is: the sample is collected on a DSC-25 instrument of TA Company of the United States; the scanning speed is 10°C / min; the protective gas is nitrogen, and the nitrogen flow rate is 50ml / min; the temperature range is room temperature to 330°C.
[0060] The thermogravimetric analysis (TGA) spectrum determination method involved in the present invention: the sample is collected on a TGA55 instrument of TA Company of the United States; the scanning speed is 10°C / min; the protective gas is nitrogen, and the nitrogen flow rate is 50ml / min; the temperature range is room temperature to 330°C.
[0061] Example 1 Preparation of Form A of γ-cyclodextrin
[0062] Weigh 200 mg of γ-cyclodextrin into a glass vial, add 0.4 ml of water, cover the lid tightly, and place it in a biochemical incubator to heat at 60°C for about 15 minutes to dissolve; filter the supernatant into a nuclear magnetic tube, add 10 mg of hydroxypropyl methylcellulose, evacuate and then pass nitrogen, cover the rubber stopper, place it in a biochemical incubator to heat at 60°C, and then set a programmed temperature rise and fall for crystallization, first keep it at 60°C for 2 hours, then cool it to 5°C at a rate of 0.1°C / min. After the program is cycled twice, keep it at 5°C for 72 hours. A white clustered solid precipitates at the bottom of the bottle and the solid is separated.
[0063] The white clustered solid prepared in Example 1 was sampled and subjected to X-ray powder diffraction. After X-ray powder diffraction pattern analysis, characteristic diffraction peaks of the crystalline form A of γ-cyclodextrin appeared, and the white clustered solid was determined to be the crystalline form A of γ-cyclodextrin. The specific results are as follows: Figure 1 shown.
[0064] The white cluster solid prepared in Example 1 was sampled and subjected to differential scanning calorimetry test. DSC spectrum analysis showed that an endothermic peak appeared at 77°C. The specific results are as follows: Figure 2 shown.
[0065] The white cluster solid prepared in Example 1 was sampled and subjected to thermogravimetric analysis. According to TGA spectrum analysis, the weight loss from room temperature to 200°C was 10%. The specific results are as follows: Figure 3 shown.
[0066] Example 2 Preparation of Form A of γ-cyclodextrin
[0067] Weigh 100 mg of γ-cyclodextrin into a glass vial, add 0.1 ml of water, cover the lid tightly, and place it in a biochemical incubator to heat at 55°C for about 18 minutes to dissolve; filter the supernatant into a nuclear magnetic tube, add 4 mg of hydroxypropyl methylcellulose, evacuate and then pass nitrogen, cover the rubber stopper, place it in a biochemical incubator to heat at 55°C, and then set a programmed temperature rise and fall for crystallization, first keep it at 55°C for 2 hours, then cool it to 8°C at a rate of 0.1°C / min. After the program is cycled 4 times, keep it at 8°C for 70 hours, and a white clustered solid will precipitate at the bottom of the bottle, and the solid will be separated.
[0068] The white clustered solid prepared in Example 2 was sampled and subjected to X-ray powder diffraction. The X-ray powder diffraction pattern analysis showed that the characteristic diffraction peaks of Form A of γ-cyclodextrin appeared, and the white clustered solid was determined to be Form A of the γ-cyclodextrin.
[0069] Example 3 Preparation of Form A of γ-cyclodextrin
[0070] Weigh 200 mg of γ-cyclodextrin into a glass vial, add 0.6 ml of water, cover the lid tightly, and place it in a biochemical incubator to heat at 65°C for about 20 minutes to dissolve; filter the supernatant into a nuclear magnetic tube, add 12 mg of hydroxypropyl methylcellulose, evacuate and then pass nitrogen, cover the rubber stopper, place it in a biochemical incubator to heat at 65°C, and then set a programmed temperature rise and fall for crystallization, first keep it at 65°C for 3 hours, then cool it to 10°C at a rate of 0.5°C / min. After the program is cycled 5 times, keep it at 10°C for 75 hours, and a white clustered solid will precipitate at the bottom of the bottle, and the solid will be separated.
[0071] The white clustered solid prepared in Example 3 was sampled and subjected to X-ray powder diffraction. The X-ray powder diffraction spectrum analysis showed that the characteristic diffraction peaks of Form A of γ-cyclodextrin appeared, and the white clustered solid was determined to be Form A of the γ-cyclodextrin.
[0072] Example 4 Preparation of γ-cyclodextrin Form A in Grams
[0073] Weigh 10.0g of γ-cyclodextrin and add it to a 100ml three-necked jacketed bottle, then measure 20ml of deionized water and add it to the three-necked jacketed bottle, protect with nitrogen, and stir at 60°C for 15min to dissolve. Then cool the reaction solution to 15°C, add 0.05g of γ-cyclodextrin seeds prepared by the method of Example 1, and after the seeds are added, set the stirring speed to 220 rpm, stir at 15°C for 1 hour, and some white solids have precipitated. Then slowly cool the reaction solution to 8°C, stir at 8°C for 2 hours, then slowly cool the reaction solution to 0°C, stir at 0°C for 4 hours, filter, collect the filter cake, and drain under reduced pressure with an oil pump to obtain 8.2g of white solid with a purity of 99.5%.
[0074] The white solid prepared in Example 4 was sampled and subjected to X-ray powder diffraction. The X-ray powder diffraction spectrum analysis showed that the characteristic diffraction peaks of Form A of γ-cyclodextrin appeared, and the white solid was determined to be Form A of the γ-cyclodextrin.
[0075] Example 5 Preparation of γ-cyclodextrin crystal form A in grams
[0076] Weigh 20.0g of γ-cyclodextrin and add it to a 100ml three-necked jacketed bottle, then measure 60ml of deionized water and add it to the three-necked jacketed bottle, protect with nitrogen, and stir at 55°C for 18min to dissolve. Then cool the reaction solution to 18°C, add 0.02g of γ-cyclodextrin seeds prepared by the method of Example 1, and after the seeds are added, set the stirring speed to 220 rpm, stir at 18°C for 1.5 hours, and some white solids have precipitated. Then slowly cool the reaction solution to 10°C, stir at 10°C for 2.5 hours, then slowly cool the reaction solution to 2°C, stir at 2°C for 4.5 hours, filter, collect the filter cake, and pump the oil pump under reduced pressure to obtain a white solid.
[0077] The white solid prepared in Example 5 was sampled and subjected to X-ray powder diffraction. The X-ray powder diffraction spectrum analysis showed that the characteristic diffraction peaks of Form A of γ-cyclodextrin appeared, and the white solid was determined to be Form A of the γ-cyclodextrin.
[0078] Example 6 Preparation of γ-cyclodextrin Form A in Grams
[0079] Weigh 15.0g of γ-cyclodextrin and add it to a 100ml three-necked jacketed bottle, then measure 15ml of deionized water and add it to the three-necked jacketed bottle, protect with nitrogen, and stir at 65°C for 20min to dissolve. Then cool the reaction solution to 20°C, add 0.06g of γ-cyclodextrin seeds prepared by the method of Example 1, and after the seeds are added, set the stirring speed to 225 rpm, stir at 20°C for 2 hours, and some white solids have precipitated. Then slowly cool the reaction solution to 12°C, stir at 12°C for 3 hours, then slowly cool the reaction solution to 4°C, stir at 4°C for 5 hours, filter, collect the filter cake, and pump the oil pump under reduced pressure to obtain a white solid.
[0080] The white solid prepared in Example 5 was sampled and subjected to X-ray powder diffraction. The X-ray powder diffraction spectrum analysis showed that the characteristic diffraction peaks of Form A of γ-cyclodextrin appeared, and the white solid was determined to be Form A of the γ-cyclodextrin.
[0081] Comparative Example 1
[0082] Weigh 10.0g of γ-cyclodextrin, add it to 100mL of deionized water, and stir to dissolve at 25-30℃. Turn on the experimental spray dryer, set the feed inlet temperature to 180℃, the discharge port temperature to 100℃, open the feed valve, spray drying ends after half an hour, collect the sample to obtain 9.76g of white powdery solid with a purity of 95.8%.
[0083] The white powder solid prepared in Comparative Example 1 was sampled and subjected to X-ray powder diffraction. The obtained X-ray powder diffraction pattern was as follows: Figure 4As shown, the spectrum has no fine peak structure, which confirms that the white powdery solid is amorphous.
[0084] Comparative Example 2
[0085] Weigh 1.0g of γ-cyclodextrin, add it to 10mL of deionized water, stir and dissolve at 25-30℃, transfer the γ-cyclodextrin aqueous solution to a crystallization surface dish, freeze it into ice, and place it in a freeze dryer for freeze drying. After 18 hours, freeze drying is completed, and the sample is collected to obtain 0.98g of white flocculent solid with a purity of 95.8%.
[0086] The white flocculent solid prepared in Comparative Example 2 was sampled and subjected to X-ray powder diffraction. Analysis of the X-ray powder diffraction spectrum showed that the spectrum had no fine peak structure, and it was determined that the white powdery solid was amorphous.
[0087] Example 7 Purification effect of Form A
[0088] The purity of the crystalline form A γ-cyclodextrin prepared in Example 4 and the amorphous γ-cyclodextrin prepared in Comparative Example 1 and Comparative Example 2 were compared. The results are shown in Table 1 below.
[0089] Table 1
[0090]
[0091]
[0092] It can be seen from Table 1 above that Form A has a certain purification effect, while the amorphous form obtained by spray drying and freeze drying has no purification effect.
[0093] Example 8 Bulk density of Form A
[0094] Experimental method (determined according to the general rule 0993 of the 2020 edition of the Chinese Pharmacopoeia for bulk density and tap density):
[0095] Bulk density determination: Take appropriate amounts of freeze-dried γ-cyclodextrin (amorphous), spray-dried γ-cyclodextrin (amorphous) and crystallized γ-cyclodextrin (crystal form A) to be tested, weigh them accurately, and slowly pour them into three glass graduated cylinders, carefully scraping the top to avoid compacting the powder. Record the apparent volume at the closest scale line, and calculate the bulk density according to formula (1):
[0096] ρB=M / V0 (1)
[0097] In formula (1), ρB is the bulk density of the fixed mass method, g / mL; M is the mass of the powder sample to be tested, g; V0 is the apparent loose volume of the powder sample to be tested, mL.
[0098] Take 3 samples from the same batch, measure them in parallel, record the readings, and take the average value as the measurement result.
[0099] Tap density determination: After the above bulk density determination method, place the measuring cylinder filled with loose powder on the bracket, tap 50 times, and record the corresponding volume V 50 , and accurate to the smallest scale, according to the formula m / V F Calculate the tap density (g / mL).
[0100] Experimental results:
[0101] The purity of the crystalline form A γ-cyclodextrin prepared in Example 1 and the amorphous γ-cyclodextrin prepared in Comparative Example 1 and Comparative Example 2 are compared. The results are shown in Table 2 below.
[0102] Table 2
[0103] Compound quality Apparent volume Loose bulk density Volume after 50 taps Tap density Crystalline Form A 2.68g 10mL 0.268g / mL 5.3mL 0.506g / mL Amorphous (spray dried) 2.209g 10mL 0.221g / mL 6.2mL 0.356g / mL Amorphous (freeze-dried) 0.745g 10mL 0.075g / mL 7.4mL 0.100g / mL
[0104] It can be seen from Table 2 above that the bulk density and tap density of Form A are greater than those of the amorphous form, which is more conducive to protecting the product from damage during packaging, reducing transportation costs and improving warehouse utilization.
[0105] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A γ-cyclodextrin, characterized in that: The γ-cyclodextrin has a crystal form A, and the crystal form A has a characteristic peak at at least one of the 2θ values selected from 9.15°±0.2°, 12.04°±0.2° or 16.35°±0.2° as determined by X-ray powder diffraction.
2. A γ-cyclodextrin according to claim 1, characterized in that: The crystalline form A has a characteristic peak at at least one of the 2θ values selected from 8.98°±0.2°, 9.15°±0.2°, 10.79°±0.2°, 11.16°±0.2°, 12.04°±0.2°, 15.73°±0.2°, 16.35°±0.2°, 18.27°±0.2° or 27.30°±0.2° as determined by X-ray powder diffraction.
3. A γ-cyclodextrin according to claim 1, characterized in that: The crystalline form A has a 2θ value selected from 4.46°±0.2°, 8.98°±0.2°, 9.15°±0.2°, 9.94°±0.2°, 10.79°±0.2°, 11.16°±0.2°, 11.90°±0.2°, 12.04°±0.2°, 14.10°±0.2°, 15.55°±0.2°, 15.73°±0.2°, 16.11°±0.2°, 17.90°±0.2°, 18.81°±0.2°, 19.70°±0.2°, 20.81°±0.2°, 21.81°±0.2°, 22.83°±0.2°, 23. At least one of 6.35°±0.2°, 16.88°±0.2°, 17.68°±0.2°, 18.27°±0.2°, 19.33°±0.2°, 20.89°±0.2°, 22.05°±0.2°, 22.41°±0.2°, 22.76°±0.2°, 23.86°±0.2°, 24.73°±0.2° or 27.30°±0.2° has a characteristic peak.
4. A γ-cyclodextrin according to claim 1, characterized in that: The crystalline form A has a 2θ value selected from 4.46°±0.2°, 5.33°±0.2°, 7.78°±0.2°, 8.98°±0.2°, 9.15°±0.2°, 9.61°±0.2°, 9.94°±0.2°, 10.63°±0.2°, 10.79°±0.2°, 11.16°±0.2°, 11.42°±0.2°, 11.55°±0.2°, 11.90°±0.2°, 12.04°±0.2°, 12.89°±0.2°, 13.12°±0.2°, .2°, 14.10°±0.2°, 14.42°±0.2°, 15.25°±0.2°, 15.55°±0.2°, 15.73°±0.2°, 16.35°±0.2°, 16.88°±0.2°, 17.68°±0.2°, 18.27°±0.2°, 19.16°±0.2°, 19.33°±0.2°, 19.64°±0.2°, 20.00°±0.2°, 20.89°±0.2°, 21.03°±0.2°, 21.75°±0.2°, 22.05°±0. 2°, 22.41°±0.2°, 22.76°±0.2°, 23.61°±0.2°, 23.86°±0.2°, 24.26°±0.2°, 24.73°±0.2°, 25.57°±0.2°, 25.75°±0.2°, 26.29°±0.2°, 26.61°±0.2°, 26.97°±0.2°, 27.30°±0.2°, 27.44°±0.2°, 28.24°±0.2°, 28.49°±0.2°, 28.66°±0.2°, 29.66°±0.2°. 2°, 30.08°±0.2°, 30.75°±0.2°, 31.71°±0.2°, 32.00°±0.2°, 32.00°±0.2°, 32.88°±0.2°, 33.21°±0.2°, 34.54°±0.2°, 34.69°±0.2°, 35.60°±0.2°, 35.86°±0.2°, 36.14°±0.2°, 38.23°±0.2°, 40.40°±0.2°, 45.94°±0.2° or 48.56°±0.2° has a characteristic peak.
5. A γ-cyclodextrin according to any one of claims 1 to 4, characterized in that: The crystal form A is also measured by differential scanning calorimetry, and the crystal form A exhibits an endothermic peak at least at 70-120° C. when measured by DSC.
6. A γ-cyclodextrin according to claim 5, characterized in that: The crystal form A decomposes at 285-295° C. as determined by DSC.
7. A γ-cyclodextrin according to any one of claims 1 to 4, characterized in that: The crystal form A is also measured by thermogravimetric analysis. The weight loss of the crystal form A when heated from room temperature to 300° C. is 10%-15% as measured by TGA.
8. A method for preparing γ-cyclodextrin according to any one of claims 1 to 7, characterized in that: The method is selected from any one of the following methods: Method (1) comprises the following steps: (11) adding water to γ-cyclodextrin, sealing the mixture, and placing the mixture in a biochemical incubator to heat the mixture until it becomes clear, thereby obtaining a clear solution; (12) filtering the clear solution and placing it in a container, adding hydroxypropyl methylcellulose to the solution, evacuating the solution and introducing nitrogen, sealing the container and placing it in a biochemical incubator for programmed temperature rise and fall crystallization, separating the precipitated white clustered solid to provide γ-cyclodextrin having a crystalline form A; Method (2) comprises the following steps: (21) heating and stirring γ-cyclodextrin and water under nitrogen protection until dissolved, and then cooling and stirring the obtained reaction solution; (22) The reaction solution after the cooling and stirring process is filtered until dry, and the filter cake is collected to provide γ-cyclodextrin having a crystalline form A.
9. The method for preparing γ-cyclodextrin according to claim 8, characterized in that: The method (1) includes any one or more of the following conditions: (111) In step (11), the ratio of the added mass of γ-cyclodextrin to the added volume of water is 1:1-3 g / mL; (112) In step (11), the heating temperature is 55-65° C.; (113) In step (11), the heating time is 15-20 min; (121) In step (12), the filtration is performed by centrifuging to separate the solid and liquid phases; (122) In step (12), the amount of hydroxypropyl methylcellulose added is 4-6% by weight of the amount of γ-cyclodextrin added; (123) In step (12), the temperature is first maintained at 55-65°C for 1-3 hours, then cooled to 5-10°C at a rate of 0.1-0.5°C / min. After the program is repeated 2-5 times, the temperature is maintained at 5-10°C for 70-75 hours.
10. The method for preparing a γ-cyclodextrin crystal form A according to claim 8, characterized in that: The method (2) includes any one or more of the following conditions: (211) In step (21), the ratio of the added mass of γ-cyclodextrin to the added volume of water is 1:1-3 g / mL; (212) In step (21), the nitrogen protection is to connect a nitrogen balloon protection device to the opening of the container; (213) In step (21), the stirring temperature is 55-65°C; (214) In step (21), the stirring time until the solution is clear is 15-20 min; (215) In step (21), the cooling and stirring procedure is to first cool the reaction solution to 15-20°C and stir for 1-2 hours, then cool it to 8-12°C and stir for 2-3 hours, and finally cool it to 0-4°C and stir for 4-5 hours; (216) In step (21), the stirring rate of the cooling stirring process is 220-250 rpm; (217) In step (21), seed crystals need to be added during the cooling and stirring procedure, and the mass percentage of the seed crystals added to the γ-cyclodextrin feed amount is 0.1-0.5%; preferably, the seed crystals are γ-cyclodextrin having crystal form A.
Citation Information
Patent Citations
Production method for gamma-cyclodextrin
CN105039462A